Leadership role in enhancing efficiency and effectiveness in organizational operations: an Islamic perspective - Ahmad, Khaliq (Routledge, 2024)
The above chapter 2 entitled, 'Leadership Role in Enhancing Efficiency and Effectiveness in Organizational Operations: An Islamic Perspective' is part of the book," Islamic Operations Management-Theories and Applications" by Prof. Rafiqul Islam et.al.. The chapter emphasizes the debate that all the managers are leaders, but all the leaders are not necessarily managers, has been captured in the literature on management and leadership. This dichotomy existed due to two reasons: the first is achieving the operational goal set by the organizations, which is assessed as effectiveness, while the second is measured in terms of efficiency.